2014
DOI: 10.1002/pmic.201400198
|View full text |Cite
|
Sign up to set email alerts
|

Changes in proteome of theΔhfqstrain derived fromFrancisella tularensisLVS correspond with its attenuated phenotype

Abstract: The posttranscriptional regulatory protein Hfq was shown to be an important determinant of the stress resistance and full virulence in the dangerous human pathogen Francisella tularensis. Transcriptomics brought rather limited clues to the precise contribution of Hfq in virulence. To reveal the molecular basis of the attenuation caused by hfq inactivation, we employed iTRAQ in the present study and compared proteomes of the parent and isogenic Δhfq strains. We show that Hfq modulates the level of 76 proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Since the most notable role of Hfq in Gram‐negative bacteria is to chaperone sRNA–mRNA interactions – by itself or along with other factors – the direct readout of its activity is to be found in protein translation (Sobrero and Valverde, ; Sobrero et al ., ; Lenco et al ., ). On this basis, we examined the effect of deleting the factor on the general protein expression profile of P. putida .…”
Section: Resultsmentioning
confidence: 97%
“…Since the most notable role of Hfq in Gram‐negative bacteria is to chaperone sRNA–mRNA interactions – by itself or along with other factors – the direct readout of its activity is to be found in protein translation (Sobrero and Valverde, ; Sobrero et al ., ; Lenco et al ., ). On this basis, we examined the effect of deleting the factor on the general protein expression profile of P. putida .…”
Section: Resultsmentioning
confidence: 97%
“…Besides FPI proteins, many other proteins with decreased synthesis implying the important HU role in metabolic processes; such as for example cell redox homeostasis, LPS biosynthesis and stress response, were identified. Among proteins with increased synthesis, for example, RNA binding protein Hfq, that acts as a global regulator of gene expression in stress tolerance and pathogenesis [ 21 ] and was found to be a positive regulator of FPI genes [ 22 ] could be mentioned. Further e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of genes from the pdp operon was upregulated at the transcriptomic level in a Δ hfq mutant strain, suggesting Hfq is their negative regulator in the wild-type context [ 43 ]. A proteomic study revealed decreased levels of the FPI proteins due to an hfq gene deletion, which explains why an hfq mutant is attenuated [ 44 ]. The importance of Hfq in stress tolerance was observed also in F. novicida [ 45 ].…”
Section: Regulators Participating In the Oxidative And Nitrosativementioning
confidence: 99%